Collective effect of single-photon scattering on the three-level atomic array. (3rd December 2018) - Tian, T.; Song, L. J.
Abstract: From the viewpoint of single-photon scattering, we investigate the collective effect of an alignment of periodically distributed V -type three-level atoms. The electromagnetic field in the free space induces the transitions between the ground state and both of the excited states, and the single-photon scattering process is formulated by the Lippmann-Schwinger equation approach. We study the reflection spectrum and find that the Lamb shift, which is induced by the collective effect of the periodically aligned atoms, is sensitive to the atomic density. Moreover, the interference between two transition channels leads to an asymmetry double-peak reflection spectrum. All of our results can be explained from the singular points of the amplitudes of the atomic excitations. Our work may be helpful to understand the recent experimental results in high-energy-photon scattering on layered nuclei materials.